HUBUNGAN ANTARA PENGETAHUAN TENTANG BAHAYA MEROKOK DENGAN STATUS MEROKOK DI “RW DENGAN RUMAH BEBAS ASAP ROKOK” KOTA YOGYAKARTA TAHUN 2016 - Agus Heri Setiawan; Yayi Suryo Prabandari; Riris Andono Ahmad (Berita Kedokteran Masyarakat (BKM), 2017)
Implementation of the smoke-free neighborhood program in YogyakartaPurposeThis study aimed to identify the successfulness of smoke-free neighborhood and to understand the relationship between the householders' knowledge and household smoking status. MethodsAn observational analytic study was conducted using cross-sectional surveys. Chi-square, Fisher exact and logistic regression tests were used to analyze the correlation between variables. ResultsFrom those numbers, qualified households which fulfill the program criteria were 76.1% and 75.9%, respectively. To be more specific, in smoke-free neighborhood, about 56.8% householders were under smoking status and 43.2% householders were identified as ex- or non-smoker. Bivariable analysis showed that there was a significant correlation between educational background, age, knowledge, and perception of householder with smoking status. The last model of multivariable analysis showed that knowledge, and age of householders was related to household smoking status. ConclusionThis study shows that smoke-free neighborhood program has not yet affected passive smoker protection significantly. A more specific controlling program to improve the knowledge especially for elderly (> 45 years old) has to be increased in smoke-free neighborhood of Yogyakarta.